2009
DOI: 10.1007/s10964-008-9391-7
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Daily Diary Study of Family Assistance and Academic Achievement Among Adolescents from Mexican, Chinese, and European Backgrounds

Abstract: A longitudinal daily diary method was employed to examine the implications of family assistance for the academic achievement of 563 adolescents (53% female) from Mexican (n = 217), Chinese (n = 206), and European (n = 140) backgrounds during the high school years (mean age 14.9 years in 9th grade to 17.8 years in 12th grade). Although changes in family assistance time within individual adolescents were not associated with simultaneous changes in their Grade Point Averages (GPAs), increases in the proportion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(105 citation statements)
references
References 20 publications
4
98
1
2
Order By: Relevance
“…In a study analyzing daily diary data, Fuligni and colleagues found that when Chinese American adolescents experienced stress at home, they were more likely to experience attendance and learning problems the following day; this was not true for Mexican American and European American adolescents (Flook & Fuligni, 2008). In addition, when Chinese American adolescents (as well as Mexican American adolescents) increased the number of days in which they provided assistance to their families over the course of high school (e.g., cleaning, caring for siblings, helping parents at work), their achievement declined (Telzer & Fuligni, 2009). This was true for both first and second generation youth.…”
Section: Barriers To High Achievementmentioning
confidence: 93%
“…In a study analyzing daily diary data, Fuligni and colleagues found that when Chinese American adolescents experienced stress at home, they were more likely to experience attendance and learning problems the following day; this was not true for Mexican American and European American adolescents (Flook & Fuligni, 2008). In addition, when Chinese American adolescents (as well as Mexican American adolescents) increased the number of days in which they provided assistance to their families over the course of high school (e.g., cleaning, caring for siblings, helping parents at work), their achievement declined (Telzer & Fuligni, 2009). This was true for both first and second generation youth.…”
Section: Barriers To High Achievementmentioning
confidence: 93%
“…On the other hand, family obligations do not just translate into increased school motivation, but also to increased levels of actual assistance to the family, including behaviors such as helping to take care of brothers and sisters and translating for parents who are not fluent in English (Hardway & Fuligni, 2006). When these demands are chronic, they can take away from the time that adolescents can put into their school work (Telzer & Fuligni, 2009). As a result, for adolescents with high levels of family obligations, academic motivation does not necessarily translate into high levels of achievement (Fuligni, Tseng, & Lam, 1999).…”
Section: High School Family Obligations and Perceptions Of Discriminamentioning
confidence: 99%
“…First, information gathered via daily diaries is likely to yield more accurate responses. Because children are asked to report on events and feelings the same day they occur-rather than weeks or months after the fact-memory biases are less likely to negatively impact recall (Telzer & Fuligni, 2009;Witkow, 2009). Second, daily diary measures allow the researcher to examine within-person associations between daily events and the outcome measure of interest.…”
Section: Daily Diary Approachmentioning
confidence: 99%